Fluktuasi Nilai Tukar Rupiah: Faktor Penyebab, Dampak, Dan Upaya Pengendaliannya - Edalmen (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2000)
Recently the value of the rupiah against the US dollar is weakened and becomes about Rp 9,000 per US dollar. This condition means that the crisis will end in the year 2000 seems to be far away. Therefore, it is a must for the government and people must work hard for the stabilization of the exchange rate of the rupiah. This article aims to examine the impact of the value of the rupiah on the Indonesian economy and suggest some critical policies to solve the problem.